L’impact de l’input et du type de tâche sur la production de la morphologie nominale en polonais par des apprenants francophones débutants - Marzena Watorek; Marie Durand; Katarzyna Starosciak (Discours)
Our study aims at analyzing the acquisition of case marking in Polish as a foreign language by beginning learners in the production of nominal forms in three different types of tasks. An imitation task and two tasks eliciting two types of discourses, a minimal discourse composed of a statement requested by a precise question and a long discourse issued from a complex verbal task. The participating learners (17 subjects) are French native speakers who have followed the same course of Polish for a total of 14 hours.    We analyze the impact of the input received by learners during classes and the impact of the type of activity on the production and acquisition of nominal morphology in Polish.    Our results show that the percentage of correctly inflected nominal forms varies depending on the task, and that the characteristics of the received input do not play the same role in the production of correct forms in each task.    The more the task is constraining the more the input characteristics play an important role and the more learners productions are correct regarding the case marking. The productions from the semi-guided task seem to depend more on communicative constraints than on formal constraints.    The present study attempts to identify the impact of the type of language activity to which the learner is requested, to perform on the production of correct answers, and to contribute to our understanding of how the input is processed at early stages of acquisition of a new language.